Корпоративная компьютерная сеть в производственно-сбытовой системе - Копаница, В. Н.; Макрушан, И. А. (My University, 2001)
Розглядаються актуальні питання функціонування логістичної системи в умовах ринкової економіки. Визначається місце корпоративної комп'ютерної мережі з позиції логістичного підходу. The topical issues of the functioning of the logistics system in a market economy are considered. The place of the corporate computer network from the point of view of the logistics approach is determined.
Keywords: корпоративная компьютерная сеть; логистическая система; эффективность корпоративной сети